Implementasi Algoritma Selection Sort dalam Membangun Aplikasi Android Pemesanan Jasa Make-up Palembang - fandhepa harahap; Irman Effendy (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Currently Make-Up Artist Service Providers still use social media such as Facebook and In-stagram in conducting transactions and offers to customers, the more orders for this Make-Up Artist service, the social media is deemed less effective for making transactions or offers because of frequent there was a fraud case from the platform which resulted in a lack of trust and security when conducting transactions or negotiations from social media, another thing was the lack of information that customers would get when ordering the Make-Up Artist services. Researchers will also apply the Selection Sort Algorithm in sorting the offer data provided by Make-Up service providers so that it is more systematic and makes it easier for customers to choose offers that suit their needs. The type of research conducted in this research is qualitative research. And the author's system development method uses the waterfall method. is a method that provides a sequential or sequential software lifeflow approach starting from analysis, design, coding, testing and support. Keywords: Make-Up Artist, Selection Sort Algorithm, waterfall